Direct ink write printing of resistive-type humidity sensors. (1st November 2021) - Yan, Feng-Jie; Huang, Wan-Qing; Sang, Xu-Hui; Liang, Jun-Ge; Wan, Xi; Shao, Feng; Gu, Xiao-Feng
Abstract: To practice the development of printed electronics, researchers need to have the access to dedicated printer of electronic materials. However, commercial printing machines require large capital investment. Direct ink write (DIW) printing on the other hand operates with single printing head and less complex system therefore is promising for tight budget projects. Herein, a DIW printing system was home-built by making modifications to a 3D printer with ready to use components. Direct pattering and minimal printing line width of 230 ± 10 µ m are demonstrated using an all solution-based Ag ink. Resistive-type humidity sensors were fabricated with DIW printed Ag electrodes and poly (diallyl dimethyl ammonium chloride) (PDDA) sensing layer. Humidity sensing performance of the sensors were examined and by taking advantage the flexibility of printing deposition, DIW printing was used to make quick modification toward a partially covered sensor structure for improved performance. Sensing response of more than 99% was obtained from 10% RH to 90% RH. Smaller hysteresis of ±4.4% RH and faster response of 7 s for adsorption and 213 s for desorption were obtained with the partially covered sensor. DIW printing is found to be a useful tool for device prototyping and ink development of printed electronics.